The Potential of Artificial Intelligence in Distance Education - Umarova Nigora Alisherovna,; Ibragimov Nukhriddin Madazimovich,; Kholisov Alisher Farkhodovich, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
The integration of Artificial Intelligence (AI) in distance education has revolutionized the way learning is delivered and experienced. AI technologies enable personalized learning paths, intelligent tutoring, automated assessments, and efficient administrative support, addressing many challenges faced by remote learners and educators. This paper explores the various applications of AI in distance education, highlights its benefits, and discusses the ethical and practical challenges associated with its implementation. The findings suggest that AI has the potential to significantly enhance the quality and accessibility of distance learning, though careful consideration of privacy, bias, and digital equity is necessary to ensure its responsible use.